Glasses antifogging cleaning gel based on nano composite material and preparation method of glasses antifogging cleaning gel

By utilizing the dynamic bond network of nanocomposite materials and photothermal triggered regeneration technology, combined with a slow-release antibacterial mechanism, the problems of light transmittance, self-healing, and long-lasting effect of anti-fog materials for eyeglasses have been solved, achieving high light transmittance, long-lasting anti-fog effect, and high antibacterial rate.

CN120944628APending Publication Date: 2025-11-14WUXI HENGQINGYA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510833635.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing anti-fog materials for eyeglasses cannot simultaneously possess high light transmittance, self-healing properties, and long-lasting anti-fog performance, and also suffer from insufficient durability.

Method used

Using nanocomposite materials, a glasses anti-fog cleaning gel is formed through a triple setup of dynamic bond network (UPy-CNC/disulfide bond) synergy, photothermal triggered regeneration (silanized Fe3O4), and sustained-release-antibacterial dual mode (microcapsules/DDAB). By utilizing a quadruple hydrogen bond and dynamic covalent bond synergistic network, combined with photothermal nanoparticles and sustained-release microcapsules, high light transmittance, self-repair, and long-lasting anti-fog effect are achieved.

Benefits of technology

It achieves 35-day long-lasting anti-fog effect, 98% self-healing rate and photothermal regeneration capability, with light transmittance maintained above 92% and antibacterial rate maintained above 95% within 30 days, significantly improving the durability and functionality of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an antifogging cleaning gel for glasses based on a nano composite material and a preparation method of the antifogging cleaning gel, and relates to the technical field of antifogging cleaning gel for glasses. Comprising the following components: a nano composite microgel matrix, modified cellulose nanocrystals, photo-thermal nanoparticles, DDAB, sustained-release microcapsules, an amphiphilic solvent and a photoinitiator, wherein the nano composite microgel matrix is prepared from acrylamide, hydroxyethyl acrylate, inorganic nano particles, 4, 4 '-dithiodibutyric acid and the balance of deionized water; the modified cellulose nanocrystals are obtained by modifying cellulose nanocrystals with ureido pyrimidone; the photo-thermal nano particles are FeO nano particles of which the surfaces are modified by a silane coupling agent; the amphiphilic solvent comprises deionized water and propylene glycol. The antifogging cleaning gel for glasses has the advantages of long-acting antifogging for 35 days, self-repairing rate greater than 98%, long-acting antibacterial ability and high light transmission performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to, in particular to, an anti-fog cleaning gel for eyeglasses based on nanocomposite materials and its preparation method. Background Technology

[0002] Glasses are prone to fogging under sudden temperature or humidity changes, leading to blurred vision. This problem is particularly pronounced during medical surgeries, laboratory procedures, outdoor sports, and everyday mask-wearing. Traditional anti-fog technologies mainly rely on physical wiping or chemical coatings, but these suffer from poor durability, limited functionality, and environmental incompatibility. Despite advancements in materials science and three generations of evolution, anti-fog technology still faces numerous technological bottlenecks.

[0003] First-generation hydrophilic coating technology: Hydrophilic coatings reduce the water contact angle (<20°), causing droplets to spread into a transparent water film. Mainstream solutions include: Polymer-inorganic composite coatings: Copolymerizing acrylamide with nano-silica to enhance hydrophilicity. However, the coating has poor abrasion resistance; after 100 wipes, the light transmittance drops from 92% to 78%, and the anti-fogging effect is <72 hours (37℃ / 90%RH environment). Polyvinyl alcohol (PVA) based films: Lock in water through a hydrogen bond network, providing significant initial anti-fogging effect. However, PVA swells and detaches at humidity >80%, and lacks antibacterial properties, easily leading to microbial contamination. This type of hydrophilic coating technology relies on physical water absorption and cannot actively eliminate moisture; it also has low mechanical strength and a short lifespan.

[0004] Second-generation superhydrophobic coating technology: Superhydrophobic coatings utilize micro-nano structures to form Cassie-Baxter states, achieving a water contact angle >150° and a roll-off angle <5°. Typical examples include: Titanium dioxide / fluorosilane composite coatings: maintaining hydrophobicity through photocatalytic decomposition of organic matter. However, the high refractive index of titanium dioxide (n=2.7) results in a light transmittance <85%, and it is highly dependent on ultraviolet light, failing in indoor environments. Hydrogel-enhanced superhydrophobic coatings (Adv. Funct. Mater., 2021): using polyacrylic acid hydrogel as a primer to improve adhesion and increase abrasion resistance to 500 wiping cycles. However, the hydrogel loses elasticity when frozen at low temperatures (<5℃), drastically reducing its anti-fogging function.

[0005] However, its light transmittance and hydrophobicity are contradictory; it has poor environmental adaptability.

[0006] Third-generation multifunctional integrated coatings: Recent research has attempted to integrate anti-fogging, antibacterial, and self-healing functions: Quaternary ammonium salt antibacterial anti-fogging film: Introducing didodecyl dimethyl ammonium bromide (DDAB), it achieves a 95% antibacterial rate against Escherichia coli. However, quaternary ammonium salts migrate rapidly, and the antibacterial rate decreases to 60% after 20 days, and it cannot repair mechanical damage. Self-healing polyurethane coating: Utilizing the synergistic effect of disulfide bonds and quadruple hydrogen bonds (UPy), the repair rate after scratching at 80℃ / 2 hours is >90%. However, its anti-fogging performance depends on the addition of glycerin (>30 wt%), resulting in stickiness and reduced light transmittance (<88%).

[0007] Therefore, there is an urgent need to develop a new material system that combines high light transmittance, self-healing, long-lasting anti-fogging, and photothermal triggered regeneration to overcome the limitations of existing technologies. Summary of the Invention

[0008] The purpose of this invention is to provide an anti-fog cleaning gel for eyeglasses based on nanocomposite materials and its preparation method, thereby improving the technical problem that existing anti-fog materials for eyeglasses cannot simultaneously possess high light transmittance, self-healing properties, and long-lasting anti-fog effects.

[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0010] The nanocomposite-based anti-fog cleaning gel for eyeglasses comprises, by weight, the following components:

[0011] 50-65 parts of nanocomposite microgel matrix; 2-5 parts of modified cellulose nanocrystals; 1-3 parts of photothermal nanoparticles; 0.5-2 parts of DDAB; 0.1-1 parts of sustained-release microcapsules; 30-50 parts of amphiphilic solvent; 0.5-1.0 parts of photoinitiator;

[0012] The nanocomposite microgel matrix includes: 5-10 parts acrylamide, 2-5 parts hydroxyethyl acrylate, 0.8-1.2 parts inorganic nanoparticles, 0.3-0.7 parts 4,4'-dithiodibutyric acid, and the balance being deionized water.

[0013] Modified cellulose nanocrystals were obtained by modifying cellulose nanocrystals with ureidopyrimidinone;

[0014] Photothermal nanoparticles are Fe3O4 nanoparticles with surfaces modified by silane coupling agents;

[0015] The amphiphilic solvents include: 18-30 parts deionized water and 12-20 parts propylene glycol.

[0016] Traditional anti-fog materials cannot simultaneously achieve high strength and high repair rate. This invention combines uridine pyrimidinone (UPy) modified cellulose nanocrystals with 4,4'-dithiodibutyric acid to form a synergistic network of quadruple hydrogen bonds and dynamic covalent bonds (-SS-). The UPy-CNC rod-like structure acts as a rigid framework, while the disulfide bonds provide flexible recombination, overcoming the limitations of being either too strong or too weak. The repair rate reaches 98.5% after scratching at 80℃ for 2 hours. Photothermal nanoparticles are heated to 50-60℃ in 5 minutes under 808 nm near-infrared light, activating the recombination of the dual dynamic bonds and promoting gel dehydration. Traditional anti-fog coatings require recoating after failure, but this solution achieves in-situ regeneration through photothermal triggering, extending the service life by 3 times. The silane layer inhibits Fe3O4 aggregation, ensuring a light transmittance of >92%. Polydopamine microcapsules encapsulate polyaminopropyl biguanide, forming a dual-mode antibacterial effect with DDAB, characterized by rapid sterilization and long-lasting sustained release. The initial DDAB inhibition rate is >99% within 24 hours; the microcapsule sustained-release period lasts 30 days, maintaining an inhibition rate of ≥95%. The hydrophilic region of the amphiphilic solvent anchors the nanogel; the hydrophobic chain binds to silanized Fe3O4, reducing light scattering.

[0017] This invention improves the long-standing contradiction between light transmittance, durability, and functionality in eyeglass anti-fog materials through a triple setting of dynamic bond network synergy (UPy-CNC / disulfide bond), photothermal triggered regeneration (silanized Fe3O4), and sustained-release-antibacterial dual mode (microcapsules / DDAB), giving it a 35-day long-lasting anti-fog effect and a self-repair rate of >98% and photothermal regeneration capability.

[0018] Furthermore, the inorganic nanoparticles include at least one of silicon dioxide, zinc oxide, or titanium oxide, with a particle size of 2 to 40 nm.

[0019] Furthermore, the Fe3O4 particle size of the photothermal nanoparticles is 10~20 nm, and 3-aminopropyltriethoxysilane is grafted onto the surface.

[0020] Furthermore, the shell of the sustained-release microcapsules is polydopamine, the core material is polyaminopropyl biguanide, and the microcapsule particle size is 200~500 nm.

[0021] Furthermore, the modified cellulose nanocrystals have a rod-like structure with an aspect ratio of 7 to 8:1, and are bonded to the nanocomposite microgel matrix through quadruple hydrogen bonds.

[0022] A preparation method applicable to the aforementioned nanocomposite-based anti-fog cleaning gel for eyeglasses includes the following steps:

[0023] S100: Inorganic nanoparticles are dispersed in deionized water, and acrylamide, hydroxyethyl acrylate, and 4,4'-dithiodibutyric acid are added. Nitrogen gas is passed through to remove oxygen. A photoinitiator is added, and ultraviolet light is irradiated for 18-22 minutes to form a nanocomposite microgel matrix.

[0024] S200: Disperse modified cellulose nanocrystals in propylene glycol and mix them evenly with the nanocomposite microgel matrix; add DDAB and photothermal nanoparticles, and stir at 42~48℃ for 1.5~2.5 hours;

[0025] S300: Add an amphiphilic solvent to the mixture obtained in step S200 and adjust the viscosity to 800~2000 cP; add polydopamine microcapsules and stir at a speed of 130~160 rpm to mix evenly.

[0026] S400, fill into a high-pressure container, and heat-treat at 58~62℃ for 1.2~1.8 hours to cure.

[0027] In step S100, after crosslinking acrylamide, hydroxyethyl acrylate, and disulfide bonds, a primary network of nanocomposite microgels is formed by UV irradiation. Traditional one-step methods result in the destruction of UPy hydrogen bonds by free radicals (loss rate >40%). This preparation method, through stepwise operations, retains >95% of the quadruple hydrogen bond activity, increasing the repair rate from 82% to 98.5%. In step S200, dynamic UPy-CNC bonds are introduced by first dispersing UPy-CNCs in propylene glycol (instead of directly adding them to the aqueous phase). Utilizing the amphiphilic nature of propylene glycol: the hydrophobic chain binds to the UPy benzene ring, inhibiting hydrogen bond pre-aggregation; the hydrophilic end promotes compatibility with the microgel matrix, achieving axially ordered arrangement of rod-shaped CNCs. In step S300, microcapsules are added with low-speed stirring to prevent polydopamine microcapsules from rupturing, achieving an encapsulation rate >95%. In step S400, the temperature is precisely matched to the disulfide bond recombination activation energy, promoting dynamic covalent bond recombination. A high-pressure environment inhibits water molecule volatilization, maintaining a stable water / propylene glycol ratio, preventing microphase separation, and reducing haze from 4.1% to 1.9%.

[0028] This preparation method improves the technical problems of dynamic bond deactivation, nano-agglomeration, microcapsule rupture, and solvent evaporation in multifunctional antifog gels through a four-stage process of stepwise photopolymerization, directional dispersion, low-pressure mixing, and high-pressure curing.

[0029] Furthermore, in step S100, the wavelength of the ultraviolet light is 315~400nm and the irradiation intensity is 25~35 mW / cm².

[0030] Furthermore, in step S200, the method for preparing modified cellulose nanocrystals includes the following:

[0031] Step 1: At 42~46℃, add microcrystalline cellulose to sulfuric acid solution and stir for 1.5~2.5h at a solid-liquid ratio of 1:14~16. Centrifuge and retain the lower precipitate. Dialyze the precipitate to neutral and then ultrasonically break it apart and freeze-dry it to obtain rod-shaped cellulose nanocrystals.

[0032] Step 2: Dissolve MIC in anhydrous THF at a solid-liquid ratio of 1:9~11, add HID dropwise, the mass ratio of MIC to HID is 1:4~7, react at 75~85℃ for 16~20h, remove THF by rotary evaporation, and recrystallize from ethanol at 0~5℃ to obtain UPy-NCO white solid.

[0033] Step 3: Disperse cellulose nanocrystals in anhydrous xylene, dehydrate at 78-82℃ for 0.8-1.2h, add UPy-NCO and DBTL, and under nitrogen protection, perform ultrasonic-assisted reaction for 7-9h. Then add anhydrous ethanol to terminate the reaction, centrifuge to collect the precipitate, wash and dry to obtain UPy-CNC.

[0034] Increasing the HDI addition to 4-7 times the MIC mass drives the reaction equilibrium to the right: conversion rate is significantly improved and the formation rate of byproduct (biuret) is significantly reduced. Low-temperature recrystallization purification: ethanol recrystallization temperature is controlled at 0-5℃, UPy-NCO purity >99%, superior to traditional room-temperature purification purity ≤95%. Ultrasonic cavitation promotes UPy-NCO penetration into CNC pores, increasing the grafting rate to 92%, while the rod-like structure breakage rate is <5%; the quadruple hydrogen bond density reaches 0.82 mmol / g. Xylene azeotropic dehydration leaves residual water <50 ppm, avoiding the consumption of -NCO by side reactions.

[0035] This preparation method achieves precise structural control of the rod-shaped CNC rod with an aspect ratio of 7~8:1 and an UPy grafting rate of 94% through a three-stage process of medium-temperature acid hydrolysis, HDI over-synthesis, and ultrasonic directional grafting; the amount of sulfuric acid used is reduced by 20% and the solvent recovery rate is >90%.

[0036] Furthermore, in step 1, the centrifugation speed is 9500~10500 rpm and the time is 12~18 min; the ultrasonic disruption power is 580~620W and the time is 25~35 min.

[0037] Centrifugation at 9500~10500 rpm breaks down colloidal stability and prevents the loss of nanocrystals; ultrasonic disruption at 580~620W utilizes cavitation energy density to fully depolymerize fiber bundles.

[0038] Furthermore, in step 2, the mass ratio of CNC, UPy-NCO, and DBTL is 1:0.2~0.5:0.01~0.03; the solid-liquid ratio of CNC, anhydrous xylene, and anhydrous ethanol is 1:95~105:9~11.

[0039] The beneficial effects of this invention are:

[0040] The formulation of this invention improves the contradiction between light transmittance, durability, and functionality in anti-fog materials for eyeglasses, giving it a 35-day long-lasting anti-fog effect, a self-repair rate of >98%, and photothermal regeneration capability. The preparation method of this invention improves the technical problems of dynamic bond deactivation, nano-agglomeration, microcapsule rupture, and solvent evaporation in multifunctional anti-fog gels, increasing the anti-fog repair rate to 99% and the 30-day long-lasting antibacterial rate to 99%.

[0041] DDAB: Didodecyl dimethylammonium bromide;

[0042] APTES: 3-Aminopropyltriethoxysilane;

[0043] MIC: 2-Amino-4-hydroxy-6-methylpyrimidine;

[0044] HID: Hexamethylene diisocyanate;

[0045] UPy-NCO: 2-Urea-4[1H]-pyrimidinone-6-isocyanate;

[0046] DBTL: Dibutyltin dilaurate;

[0047] CNC: Cellulose nanocrystals;

[0048] UPy-CNC: Ureidinidone-cellulose nanocrystals. Detailed Implementation

[0049] Example 1

[0050] The preparation methods for modified cellulose nanocrystals include the following:

[0051] Step 1: At 45℃, add 20g of microcrystalline cellulose to 300mL of 64% sulfuric acid solution and stir for 2h. Centrifuge at 10000rpm for 15min. Retain the lower precipitate, dialyze the precipitate to neutral, and then ultrasonically break it apart at 600W for 30min. Freeze-dry to obtain rod-shaped cellulose nanocrystals.

[0052] Step 2: Dissolve 10g MIC in 100mL anhydrous THF, add 60g HID dropwise, react at 80℃ for 18h, remove THF by rotary evaporation, and recrystallize from ethanol at 2.5℃ to obtain UPy-NCO white solid;

[0053] Step 3: Disperse 10g of cellulose nanocrystals in 1000mL of anhydrous xylene, dehydrate at 80℃ for 1h, add 3g of UPy-NCO and 0.2g of DBTL, and react under nitrogen protection with ultrasonic assistance at 580W for 8h. Then add 100mL of anhydrous ethanol to terminate the reaction, collect the precipitate by centrifugation, wash 3 times with a mixed solvent of 2L acetone and 1.5L ethanol, and dry to obtain UPy-CNC.

[0054] Example 2

[0055] The preparation methods for modified cellulose nanocrystals include the following:

[0056] Step 1: At 42℃, 20g of microcrystalline cellulose was added to 280mL of 64% sulfuric acid solution and stirred for 1.5h. The mixture was then centrifuged at 95000rpm for 12min. The lower precipitate was retained, dialyzed to neutral, and then ultrasonically broken and dispersed at 580W for 25min. Finally, it was freeze-dried to obtain rod-shaped cellulose nanocrystals.

[0057] Step 2: Dissolve 10g MIC in 900mL anhydrous THF, add 40g HID dropwise, react at 7℃ for 1h, remove THF by rotary evaporation, and recrystallize from ethanol at 0℃ to obtain UPy-NCO white solid.

[0058] Step 3: Disperse 10g of cellulose nanocrystals in 950mL of anhydrous xylene, dehydrate at 78℃ for 0.8h, add 2g of UPy-NCO and 0.1g of DBTL, and react under nitrogen protection with ultrasonic assistance at 620W for 7h. Then add 95mL of anhydrous ethanol to terminate the reaction, collect the precipitate by centrifugation, wash 3 times with a mixed solvent of 1.5L acetone and 1.5L ethanol, and dry to obtain UPy-CNC.

[0059] Example 3

[0060] The preparation methods for modified cellulose nanocrystals include the following:

[0061] Step 1: At 46℃, add 20g of microcrystalline cellulose to 320mL of 64% sulfuric acid solution and stir for 2.5h. Centrifuge at 10500rpm for 18min. Retain the lower precipitate, dialyze the precipitate to neutral, and then ultrasonically break it apart at 620W for 35min. Freeze-dry to obtain rod-shaped cellulose nanocrystals.

[0062] Step 2: Dissolve 10g MIC in 1100mL anhydrous THF, add 70g HID dropwise, react at 85℃ for 20h, remove THF by rotary evaporation, and recrystallize from ethanol at 5℃ to obtain UPy-NCO white solid.

[0063] Step 3: Disperse 10g of cellulose nanocrystals in 1050mL of anhydrous xylene, dehydrate at 82℃ for 1.2h, add 5g of UPy-NCO and 0.03g of DBTL, and react under nitrogen protection with ultrasonic assistance at 600W for 9h. Then add 105mL of anhydrous ethanol to terminate the reaction, collect the precipitate by centrifugation, wash 3 times with a mixed solvent of 1L acetone and 1.5L ethanol, and dry to obtain UPy-CNC.

[0064] Comparative Example 1

[0065] The preparation methods for modified cellulose nanocrystals include the following:

[0066] Step 1: At 50℃, add 20g of microcrystalline cellulose to 300mL of 64% sulfuric acid solution and stir for 2h. Centrifuge at 10000rpm for 15min. Retain the lower precipitate, dialyze the precipitate to neutral, and then ultrasonically break it apart at 800W for 30min. Freeze-dry to obtain rod-shaped cellulose nanocrystals.

[0067] Step 2: Dissolve 10g MIC in 100mL anhydrous THF, add 30g HID dropwise, react at 80℃ for 18h, remove THF by rotary evaporation, and recrystallize from ethanol at room temperature to obtain UPy-NCO white solid.

[0068] Step 3: Disperse 10g of cellulose nanocrystals in 1000mL of anhydrous xylene, dehydrate at 80℃ for 1h, add 5g of UPy-NCO and 0.5g of DBTL, and react under nitrogen protection with ultrasonic assistance at 800W for 8h. Then add 100mL of anhydrous ethanol to terminate the reaction, collect the precipitate by centrifugation, wash 3 times with a mixed solvent of 2L acetone and 1.5L ethanol, and dry to obtain UPy-CNC.

[0069] The product performance parameters of Examples 1-3 and Comparative Example 1 are shown in Table 1.

[0070] Table 1 Performance parameters of products from Examples 1-3 and Comparative Example 1

[0071] Performance parameters Aspect Ratio UPy-NCO purity Grafting rate Hydrogen bond density (mmol / g) 80℃ repair rate Example 1 8:1 99.5% 94% 0.82 98.5% Example 2 7.5:1 99.1% 91% 0.80 96% Example 3 7:1 99.2% 93% 0.78 97% Comparative Example 1 4:1 82% 68% 0.45 72%

[0072] As shown in Table 1, in Examples 1-3, the hydrolysis temperature was 42-46℃ to ensure the full dissolution of the amorphous cellulose region. High-speed centrifugation removed degradation fragments while retaining the intact crystalline region. The synergistic effect of these two methods resulted in a high aspect ratio of 7-8:1, providing more active sites for UPy grafting. Excess HDI propelled the reaction towards UPy-NCO formation. Ethanol recrystallization at 0-5℃ suppressed impurity precipitation and synergistically produced UPy-NCO with a purity >99%, ensuring grafting efficiency. Ultrasonic dispersion at 580-620W opened the CNC pores through cavitation, allowing UPy-NCO to permeate and graft, precisely catalyzing the -NCO / -OH reaction and avoiding excessive cross-linking. The grafting rate was 91%, and the rod-like structure integrity rate was >95%. The mass ratio of CNC, UPy-NCO, and DBTL was controlled at 1:0.2-0.5:0.01-0.03 to ensure a low byproduct rate. The modified cellulose nanocrystals prepared in this invention achieved a repair rate ≥96% at 80℃. The modified cellulose nanocrystals prepared in Examples 1-3 of this invention have significantly better performance parameters than those in Comparative Example 1.

[0073] Example 4

[0074] The eyeglass anti-fog cleaning gel based on nanocomposite materials comprises the following components:

[0075] Acrylamide 80g, hydroxyethyl acrylate 30g, silica (particle size 20nm) 10g, 4,4'-dithiodibutyric acid 5g, deionized water 475g; modified cellulose nanocrystals prepared by the method in Example 1: 30g; modified Fe3O4 nanoparticles: 20g, particle size 15nm; DDAB: 18g; sustained-release microcapsules (particle size 350nm): 5g; in amphiphilic solvents: deionized water 240g, propylene glycol 160g; photoinitiator 2959: 8g.

[0076] A preparation method applicable to the aforementioned nanocomposite-based anti-fog cleaning gel for eyeglasses includes the following steps:

[0077] S100: Inorganic nanoparticles are dispersed in deionized water, and acrylamide, hydroxyethyl acrylate, and 4,4'-dithiodibutyric acid are added. Nitrogen gas is passed through to remove oxygen. A photoinitiator is added, and ultraviolet light is irradiated for 20 minutes at an intensity of 30 mW / cm² to form a nanocomposite microgel matrix.

[0078] S200: Disperse modified cellulose nanocrystals in propylene glycol and mix them evenly with the nanocomposite microgel matrix; add DDAB and photothermal nanoparticles, and stir at 45°C for 2 hours;

[0079] S300: Add an amphiphilic solvent to the mixture obtained in step S200 and adjust the viscosity to 1500 cP; add polydopamine microcapsules and stir at 150 rpm to mix.

[0080] S400, fill into a high-pressure container, and heat-treat at 60°C for 1.5 hours to cure.

[0081] Example 5

[0082] The eyeglass anti-fog cleaning gel based on nanocomposite materials comprises the following components:

[0083] Acrylamide 50g, hydroxyethyl acrylate 20g, zinc oxide (particle size 2nm) 8g, 4,4'-dithiodibutyric acid 3g, deionized water 419g; modified cellulose nanocrystals prepared by the method in Example 1: 20g; modified Fe3O4 nanoparticles: 10g, particle size 10 nm; DDAB: 5g; sustained-release microcapsules (particle size 200 nm): 1g; photoinitiator 2959: 5g; amphiphilic solvents: deionized water 180g, propylene glycol 120g.

[0084] A preparation method applicable to the aforementioned nanocomposite-based anti-fog cleaning gel for eyeglasses includes the following steps:

[0085] S100: Inorganic nanoparticles are dispersed in deionized water, and acrylamide, hydroxyethyl acrylate, and 4,4'-dithiodibutyric acid are added. Nitrogen gas is passed through to remove oxygen. A photoinitiator is added, and ultraviolet light is irradiated for 18 minutes at an intensity of 25 mW / cm² to form a nanocomposite microgel matrix.

[0086] S200: Disperse modified cellulose nanocrystals in propylene glycol and mix them evenly with the nanocomposite microgel matrix; add DDAB and photothermal nanoparticles, and stir at 42°C for 1.5 hours;

[0087] S300: Add an amphiphilic solvent to the mixture obtained in step S200 and adjust the viscosity to 800 cP; add polydopamine microcapsules and stir at 130 rpm to mix.

[0088] S400, fill into a high-pressure container, and heat-treat at 58°C for 1.2 hours to cure.

[0089] Example 6

[0090] The eyeglass anti-fog cleaning gel based on nanocomposite materials comprises the following components:

[0091] Acrylamide 100g, hydroxyethyl acrylate 50g, titanium dioxide (particle size 40nm) 12g; 4,4'-dithiodibutyric acid 7g, deionized water 481g; modified cellulose nanocrystals prepared by the method of Example 1 50g; modified Fe3O4 nanoparticles 30g, particle size 20 nm; DDAB: 20g; sustained-release microcapsules (particle size 500 nm) 10g; photoinitiator 2959: 10g; in the amphiphilic solvent, deionized water 300g, propylene glycol 200g.

[0092] A preparation method applicable to the aforementioned nanocomposite-based anti-fog cleaning gel for eyeglasses includes the following steps:

[0093] S100: Inorganic nanoparticles are dispersed in deionized water, and acrylamide, hydroxyethyl acrylate, and 4,4'-dithiodibutyric acid are added. Nitrogen gas is passed through to remove oxygen. A photoinitiator is added, and ultraviolet light is irradiated for 22 minutes at an intensity of 35 mW / cm² to form a nanocomposite microgel matrix.

[0094] S200: Disperse modified cellulose nanocrystals in propylene glycol and mix them evenly with the nanocomposite microgel matrix; add DDAB and photothermal nanoparticles, and stir at 48°C for 2.5 hours;

[0095] S300: Add an amphiphilic solvent to the mixture obtained in step S200 and adjust the viscosity to 2000 cP; add polydopamine microcapsules and stir at 160 rpm to mix.

[0096] S400, fill into a high-pressure container, and heat-treat at 62°C for 1.8 hours to cure.

[0097] Comparative Example 2

[0098] The eyeglass anti-fog cleaning gel based on nanocomposite materials comprises the following components:

[0099] Acrylamide 80g, hydroxyethyl acrylate 30g, silica (particle size 20nm) 10g, 4,4'-dithiodibutyric acid 5g, deionized water 475g; modified cellulose nanocrystals prepared by the method in Example 1: 30g; modified Fe3O4 nanoparticles: 20g, particle size 15nm; DDAB: 25g; sustained-release microcapsules (particle size 350nm): 5g; in amphiphilic solvents: deionized water 240g, propylene glycol 160g; photoinitiator 2959: 8g.

[0100] A preparation method applicable to the aforementioned nanocomposite-based anti-fog cleaning gel for eyeglasses includes the following steps:

[0101] S100: Inorganic nanoparticles are dispersed in deionized water, and acrylamide, hydroxyethyl acrylate, and 4,4'-dithiodibutyric acid are added. Nitrogen gas is passed through to remove oxygen. A photoinitiator is added, and ultraviolet light is irradiated for 10 minutes at an intensity of 30 mW / cm² to form a nanocomposite microgel matrix.

[0102] S200: Disperse modified cellulose nanocrystals in propylene glycol and mix them evenly with the nanocomposite microgel matrix; add DDAB and photothermal nanoparticles, and stir at 50°C for 2 hours;

[0103] S300: Add an amphiphilic solvent to the mixture obtained in step S200 and adjust the viscosity to 1500 cP; add polydopamine microcapsules and stir at 250 rpm to mix well.

[0104] S400, fill into an atmospheric pressure container, and heat-treat at 60°C for 1.5 hours to cure.

[0105] The performance parameters of the products in Examples 4-6 and Comparative Example 2 are shown in Table 2.

[0106] Table 2 Performance parameters of products from Examples 4-6 and Comparative Example 2

[0107] Performance parameters transmittance % Repair rate % Anti-fog duration / day 30-day antibacterial rate Wear resistance times Example 4 92.5 99.2 35 99% 500 Example 5 93.5 99.0 28 95% 460 Example 6 90.8 98.5 32 98% 450 Comparative Example 2 86.3 82 7 68% 100

[0108] As shown in Table 2, the anti-fog cleaning gels prepared in Examples 4-6 have a light transmittance of 92.5%, significantly better than the 86.3% of Comparative Example 2; a repair rate of 99.2%, significantly better than the 82% of Comparative Example 2; an anti-fog duration extended to 35 days, 28 days longer than Comparative Example 2; a 30-day antibacterial rate of 99%, far higher than the 68% of Comparative Example 2; and a wear resistance of up to 500 cycles, 400% more than Comparative Example 2. This demonstrates that the preparation method of the anti-fog cleaning gel for glasses in this invention, specifically the ultraviolet light irradiation time in step 1, the low-temperature stirring in step 2, the low-speed stirring and mixing of polydopamine microcapsules in step 3, and the high-pressure curing in step 4, can work synergistically to significantly improve the performance of the anti-fog cleaning gel for glasses compared to Comparative Example 2.

[0109] Examples 4-6 and the preparation method of the polydopamine microcapsules used in Comparative Example 2 include the following steps:

[0110] Preparation of PDMS silicone oil template: Add 0.25 mL of DMDES and 0.25 mL of 25% ammonia water to a glass bottle and shake by hand for 1 minute (frequency 3 Hz); let stand at 25℃ for 6 hours to hydrolyze and form milky white PDMS silicone oil droplets (particle size 1.5±0.3 μm).

[0111] O / W emulsion construction: Add 0.5 mL of polyaminopropyl biguanide to the above system; ultrasonically disperse (power 300 W, frequency 40 kHz) for 5 minutes to form a homogeneous emulsion (droplet diameter 2.0 ± 0.5 μm).

[0112] In-situ polymerization of PDA: 20 mg of dopamine hydrochloride was dissolved in 10 mL of Tris-HCl buffer (pH 8.5); poured into the emulsion system and placed on a magnetic stirrer (900 rpm); reacted at 15°C for 24 hours (in the dark), and PDA was deposited on the surface of the droplets to form a shell.

[0113] Post-processing: Centrifuge (4000 rpm, 10 minutes), discard supernatant; wash precipitate 3 times with deionized water; freeze-dry at -50℃ for 24 hours after quick-freezing with liquid nitrogen to obtain black powder microcapsules.

[0114] Examples 4-6 and the preparation method of silanized modified Fe3O4 used in Comparative Example 2 include the following steps:

[0115] Synthesis of Fe3O4 nanoparticles:

[0116] Raw materials: FeCl3·6H2O and FeCl2·4H2O (molar ratio 2:1), dissolved in 0.4 mol / L HCl.

[0117] Procedure: Add iron salt solution dropwise to 0.7 mol / L ammonia water, stir at 30–35℃ for 60 minutes (250–300 rpm); magnetically separate the precipitate, wash until neutral, and vacuum dry.

[0118] Surface silanization modification:

[0119] Reagents: silane coupling agent APTES, solvent ethanol.

[0120] Steps: Disperse Fe3O4 in 50-100 parts of anhydrous ethanol and sonicate for 30 minutes; add 1-2 parts of APTES, control the pH of the system to 5-6, and reflux at 80-120℃ for 18-24 hours under nitrogen protection; perform magnetic separation, wash three times with ethanol, and dry to obtain aminated Fe3O4.

Claims

1. A glasses anti-fog cleaning gel based on nanocomposite materials, characterized in that, By weight, it includes the following components: Nanocomposite microgel matrix: 50-65 parts, modified cellulose nanocrystals: 2-5 parts, photothermal nanoparticles: 1-3 parts, DDAB: 0.5-2 parts, sustained-release microcapsules: 0.1-1 parts, amphiphilic solvent: 30-50 parts, photoinitiator: 0.5-1.0 parts; The nanocomposite microgel matrix includes: 5-10 parts acrylamide, 2-5 parts hydroxyethyl acrylate, 0.8-1.2 parts inorganic nanoparticles, 0.3-0.7 parts 4,4'-dithiodibutyric acid, and the balance being deionized water. The modified cellulose nanocrystals were obtained by modifying cellulose nanocrystals with ureidopyrimidinone; Photothermal nanoparticles are Fe3O4 nanoparticles with surfaces modified by silane coupling agents; The amphiphilic solvents include: 18-30 parts deionized water and 12-20 parts propylene glycol.

2. The eyeglass anti-fog cleaning gel based on nanocomposite materials according to claim 1, characterized in that, Inorganic nanoparticles include at least one of silicon dioxide, zinc oxide, or titanium oxide, with a particle size of 2 to 40 nm.

3. The eyeglass anti-fog cleaning gel based on nanocomposite materials according to claim 1, characterized in that, The photothermal nanoparticles have a Fe3O4 particle size of 10~20 nm and are grafted with 3-aminopropyltriethoxysilane on their surface.

4. The eyeglass anti-fog cleaning gel based on nanocomposite materials according to claim 1, characterized in that, The shell of the sustained-release microcapsules is polydopamine, the core material is polyaminopropyl biguanide, and the microcapsule particle size is 200~500 nm.

5. The eyeglass anti-fog cleaning gel based on nanocomposite materials according to claim 1, characterized in that, The modified cellulose nanocrystals have a rod-like structure with an aspect ratio of 7 to 8:1, and are bonded to the nanocomposite microgel matrix through quadruple hydrogen bonds.

6. A preparation method, characterized in that, An eyeglass anti-fog cleaning gel based on nanocomposite materials as described in any one of claims 1 to 5, comprising the following steps: S100: Inorganic nanoparticles are dispersed in deionized water, and acrylamide, hydroxyethyl acrylate, and 4,4'-dithiodibutyric acid are added. Nitrogen gas is passed through to remove oxygen. A photoinitiator is added, and ultraviolet light is irradiated for 18-22 minutes to form a nanocomposite microgel matrix. S200: Disperse modified cellulose nanocrystals in propylene glycol and mix them evenly with the nanocomposite microgel matrix; add DDAB and photothermal nanoparticles, and stir at 42~48℃ for 1.5~2.5 hours; S300: Add an amphiphilic solvent to the mixture obtained in step S200 and adjust the viscosity to 800~2000 cP; add polydopamine microcapsules and stir at a speed of 130~160 rpm to mix evenly. S400, fill into a high-pressure container, and heat-treat at 58~62℃ for 1.2~1.8 hours to cure.

7. The preparation method according to claim 5, characterized in that, In step S100, the wavelength of the ultraviolet light is 315~400nm and the irradiation intensity is 25~35 mW / cm².

8. The preparation method according to claim 5, characterized in that, In step S200, the preparation method of modified cellulose nanocrystals includes the following: Step 1: At 42~46℃, add microcrystalline cellulose to sulfuric acid solution and stir for 1.5~2.5h at a solid-liquid ratio of 1:14~16. Centrifuge and retain the lower precipitate. Dialyze the precipitate to neutral and then ultrasonically break it apart and freeze-dry it to obtain rod-shaped cellulose nanocrystals. Step 2: Dissolve MIC in anhydrous THF at a solid-liquid ratio of 1:9~11, add HID dropwise, the mass ratio of MIC to HID is 1:4~7, react at 75~85℃ for 16~20h, remove THF by rotary evaporation, and recrystallize from ethanol at 0~5℃ to obtain UPy-NCO white solid. Step 3: Disperse cellulose nanocrystals in anhydrous xylene, dehydrate at 78-82℃ for 0.8-1.2h, add UPy-NCO and DBTL, and under nitrogen protection, perform ultrasonic-assisted reaction for 7-9h. Then add anhydrous ethanol to terminate the reaction, centrifuge to collect the precipitate, wash and dry to obtain UPy-CNC.

9. The preparation method according to claim 8, characterized in that, In step 1, the centrifugation speed is 9500~10500 rpm and the time is 12~18 min; the ultrasonic disruption power is 580~620W and the time is 25~35 min.

10. The preparation method according to claim 8, characterized in that, In step 3, the mass ratio of CNC, UPy-NCO, and DBTL is 1:0.2~0.5:0.01~0.03; the solid-liquid ratio of CNC, anhydrous xylene, and anhydrous ethanol is 1:95~105:9.5~10.5.